Russian Reception by James Hogg (Mid-19th — Early 20th Centuries) - D. N. Zhatkin (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The article continues a series of works devoted to the Russian reception of the Scottish writer James Hogg (1770—1835), a famous interpreter of folk ballads and author of “The Private Memoirs and Confessions of a Justified Sinner” (1824). The facts and materials related to the perception of J. Hogg in Russia in the middle of the XIX — early XX century are collected and summarized. It is noted that during the period under review, no new translations of J. Hogg's poetry and prose into Russian were created, however, in the articles of leading literary critics (N. G. Chernyshevsky, M. L. Mikhailov, A. V. Druzhinin) when analyzing the works of N. V. Gogol, T. Goode, the translation activity of I. S. Turgenev expressed opinions on certain aspects of the biography and work of the Scottish author. It has been established that the main source of information about J. Hogge and his work was for the Russian reader of the second half of the 19th — early 20th centuries translated publications on the history of English literature and culture, other books by Western European researchers published in Russia. The manifestations of interest of Russian researchers and popularizers of English literature in the work of J. Hogg are comprehended, with special attention paid to the article by N. A. Solovyov-Nesmelov “James Hogg”, which was a literary sketch about the childhood of the writer, and the essay by K. F. Tiander the novel of the first quarter of the 19th century, which offers a different assessment from the predecessors of the Scottish author’s activities as a continuer of the traditions of M. Edgeworth.